DESIGN AND DEVELOPMENT OF LOSARTAN POTASSIUM FLOATING DRUG DELIVERY SYSTEMS - Mohapatra, Prasanta Kumar; Prathibha, Ch.; Tomer, Vivek; Gupta, Mandeep Kumar; Sahoo, Satyajit (International Journal of Applied Pharmaceutics, 2018)
Objective: The current study was projected to prepare a losartan potassium gastroretentive drug delivery system (GRDDS) of floating tablets was planned to enhance the gastric residence time, thus prolong the drug release. Methods: Effervescent floating matrix tablets of losartan potassium were prepared by direct compression technique using polymers like HPMC k4m, guar gum, and gum karaya, with lubricants magnesium stearate and talc. In the present study, sodium bicarbonate was incorporated as a gas generating agent. Total nine formulations were designed and evaluated for pre-compression parameters known as the angle of repose, bulk density, tapped density, Hausner's ratio, compressibility index, and post-compression parameters are uniformity of weight, hardness, and drug content percentage, variability, in vitro buoyancy, dissolution studies, and Fourier transform infrared spectroscopy (FTIR). Results: An in vitro dissolution study was carried out by using buffer pH 1.2. From in vitro dissolution studies, it has been found that an increase in polymer concentration diminishes the drug release profile. The in vitro drug release percentage from F4-F9 formulations ranged from 60.28%-98.66% at the closing of 12 h and buoyancy found over 12 h. Conclusion: The in vitro drug release from F1-F3 and F7-F9 followed zero-order, F4 followed Higuchi order, F5 and F6 followed Hixon-Crowell release kinetics. The drug release mechanism was set up to be F1-F8 non-Fickian (anomalous behavior) and F9 having Fickian diffusion type.